Architectural Distortion on Digital Breast Tomosynthesis: Management Algorithm and Pathological Outcome. Issue 5 (8th July 2020) - Samreen, Naziya; Moy, Linda; Lee, Cindy S
Abstract: Architectural distortion on digital breast tomosynthesis (DBT) can occur due to benign and malignant causes. With DBT, there is an increase in the detection of architectural distortion compared with 2D digital mammography, and the positive predictive value is high enough to justify tissue sampling when imaging findings are confirmed. Workup involves supplemental DBT views and ultrasound, with subsequent image-guided percutaneous biopsy using the modality on which it is best visualized. If architectural distortion is subtle and/or questionable on diagnostic imaging, MRI may be performed for problem solving, with subsequent biopsy of suspicious findings using MRI or DBT guidance, respectively. If no suspicious findings are noted on MRI, a six-month follow-up DBT may be performed. On pathology, malignant cases are noted in 6.8%–50.7% of the cases, most commonly due to invasive ductal carcinoma, followed by invasive lobular carcinoma. Radial scars are the most common benign cause, with stromal fibrosis and sclerosing adenosis being much less common. As there is an increase in the number of benign pathological outcomes for architectural distortion on DBT compared with 2D digital mammography, concordance should be based on the level of suspicion of imaging findings. As discordant cases have upgrade rates of up to 25%, surgical consultation is recommended for discordant radiologic-pathologic findings.